Antigent Type Variation of Salmonella Pullorum Found in Indonesiaand the Spread of Salmonella Serotypes in Chicken - Poernomo, J Sri (Indonesian Animal Sciences Society, 2004)
Salmonella pullorum (0,, 9,, 2 antigen structure) is the cause of pullorum disease attacking young ages under a month with a mortality rate between 20% and 80% and adult chickens act as carriers. The disease is spread horizontally and vertically trough the eggs from the hens to their chicks . Treatment with antibiotics and sulfa only reduces the infection, but it can not break the spreading cycle. The disease can be eliminated by conducting pullorum test on hens prior to egg laying . Hens with positive results (reactors) must be killed/removed from the farms. Pullorum antigen is made from S. pullorum . Suspension S. Pullorum has a somatic antigen structure (O) with varied factor 12 consisting of 12 1, 122 and 123 fractions thereby we recognize S. pullorum standard, i.e . S. pullorum possessing antigen structure with fraction 12 3 dominant, variant with fraction 122 dominant and intermediate of balance 12 2 and 123 If chickens in the field infected by S. pullorum variants are tested with S. Pullorum antigen standard, it is not detected and vice versa. Therefore, Pullorum antigen must contain S. pullorum antigen standard and variant known as polyvalent Pullorum antigen. In Indonesia, from 1971 to 1982, 25 isolates were isolated from fauns in Bogor, Jakarta, Bandung and Medan, and after bring tested serologically (fast agglutination) there were 5 isolates of S. Pullorum standard, 14 isolates of S. pullorum variant, 1 of the S. pullorum intermediate, and 5 isolates of rough shapes. Therefore, the Pullorum antigens used in Indonesia and the world generally colored polyvalent antigen S. pullorum standard and S. Pullorum and S. pullorum variant. In this paper, it is also reported the spread of Salmonella serotypes tested by at Research Institute for Veterinary Science from 1984 to 2003 . Key words: Salmonella pullorum, chicken, antigen S. pullorum